2005
DOI: 10.1523/jneurosci.2149-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Specific Associative Long-Term Potentiation Induced by a Sleep Spindle-Related Spike Train

Abstract: Spindles are non-rapid eye movement (non-REM) sleep EEG rhythms (7-14 Hz) that occur independently or in association with slow oscillations (0.6 -0.8 Hz). Despite their proposed function in learning and memory, their role in synaptic plasticity is essentially unknown. We studied the ability of a neuronal firing pattern underlying spindles in vivo to induce synaptic plasticity in neocortical pyramidal cells in vitro. A spindle stimulation pattern (SSP) was extracted from a slow oscillation upstate that was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
290
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(295 citation statements)
references
References 64 publications
5
290
0
Order By: Relevance
“…identified for this age range. Nonetheless, slow and fast spindles have been associated with hippocampal reactivation and plasticity (34)(35)(36)(37)(38), and studies in young adults have found an association between spindles and learning (24,39,40). Likewise, we posit that in preschool children, spindles may mark hippocampal-neocortical interactions, a process underlying the stabilization and consolidation of the memory.…”
Section: Discussionmentioning
confidence: 74%
“…identified for this age range. Nonetheless, slow and fast spindles have been associated with hippocampal reactivation and plasticity (34)(35)(36)(37)(38), and studies in young adults have found an association between spindles and learning (24,39,40). Likewise, we posit that in preschool children, spindles may mark hippocampal-neocortical interactions, a process underlying the stabilization and consolidation of the memory.…”
Section: Discussionmentioning
confidence: 74%
“…Increasingly, sleep spindles, one of the most prominent features of NREM, have been implicated in these plastic processes (5,7,8,17,29). It has been postulated that spindles facilitate synaptic plasticity in cortical cells via calcium-dependent mechanisms (11), and it has been shown that cortical stimulation at the spindle frequency increases synaptic plasticity (30). If spindles are truly the carriers of memory consolidation, then they must act specifically on local circuits.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that spindle activity sets the conditions for synaptic changes by favoring calcium entry into the cell and initiation of plasticity-related intracellular cascades (Sejnowski and Destexhe, 2000;Lisman et al, 2002;Benington and Frank, 2003). Indeed, a neuronal firing pattern corresponding to spindle oscillations in vivo has been reported recently to induce synaptic potentiation in neocortical pyramidal cells in vitro (Rosanova and Ulrich, 2005). Thus, increased density of cortical spindles can promote synaptic reinforcement in networks that have been actively engaged during learning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had focused on the rapid eye movement (REM) phase; slow-wave sleep (SWS) has been strongly implicated now, as well (for review, see Gais and Born, 2004;Rauchs et al, 2005;Walker and Stickgold, 2006). Sleep spindles, 12-15 Hz oscillations superimposed on slow waves , may promote neural plasticity underlying learning and memory (Steriade and Timofeev, 2003;Rosanova and Ulrich, 2005). Moreover, there is recent evidence for an increase in spindle density after verbal learning Clemens et al, 2005) or motor learning (Smith and MacNeill, 1994;Meier-Koll et al, 1999;Fogel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%